Anti-Rhetorical Strategies in Early Modern Images of Comic Actors: Harlequin’s Iconography and its Surviving Medieval Features - Pietrini, Sandra (Early Modern Culture Online, 2018)
The Compositions de Rhétorique by Tristano Martinelli were published in 1600 as a present to Maria de’ Medici for her marriage. The book is composed by blank pages interposed by images and the frontispice shows the famous actor as an almost hellish figure, bearing a pannier full of little Harlequins. A similar iconography pattern is to be seen in theRecueil Fossard, though as part of a dramatic context, and could ultimately derive from the iconography of Hellequin, as it is shown in a miniature of the Roman the Fauvel, where the hellish figure leads a cart with dead unchristened children. Discussing the hellish origin of Harlequin, most of scholars have neglected the evidence that some of his attributes are rooted in the sinful world of medieval entertainment. The pannier full of little kids or apes, for instance, recurs in medieval iconography of jesters, and since the XIVth century it begins to occur also in the depictions of devils, who assume some comical connotations. Exploring the context of medieval miniatures in relation to later iconography of actors, the article aims at rediscussing the vexed question of the hellish origin of Harlequin, providing some examples of a puzzling intertwining of elements and patterns.